Considerations concerning the practice of caring for Moroccan immigrants - Isabel Gentil García (Universidad de Alicante, 2012)
Nursing has a need for knowledge in order to approach the new challenges faced by a so different current social reality, which urges us to care for people of other cultures. This work aims to provide some keys for the improvement of our performance and to obtain higher efficiency regarding health care given to Moroccan immigrants. This work is the result of a qualitative research and interviews carried out within my experience with immigrant Moroccan population. As a conclusion, the perception and experiences of health and disease vary according to the culture of origin, and our professional experience cannot be extended in an equal manner to individuals of different cultures.